Fast encoding algorithm avoiding repetition of motion estimation in scalable video coding - Park, C-S; Jung, S-W; Choi, K-S; Ko, S-J (Electronics letters, 2010)
Proposed in this paper is a fast encoding algorithm which avoids repetition of the motion estimation process in the current scalable video coding (SVC) codec. Experimental results show that the proposed algorithm can reduce encoding time by 29.69%-37.80%, while the coding performance of the SVC codec adopting the proposed algorithm is exactly the same as that of the original one.